ANALISIS MOTIVASI BERDASARKAN GENDER DAN JENIS OLAHRAGA - Hadyansah , Diky (STKIP Pasundan, 2019)
This study aims to describe the motivation of STKIP Pasundan Cimahi students in participating in sports UKM activities. The method used is descriptive quantitative method. The study population was STKIP Pasundan Cimahi students majoring in Physical Education, Health and Recreation (PJKR) with a sample of students sitting at level one, two, and three as many as 148 people. The sampling technique uses probability sampling techniques namely Proportionate Stratified Random Sampling. The data collection techniques using motivational instrument questionnaires developed refer to the dimensions of the concept developed by Decy & Ryan (1985, 2000) which Hidayat then adapted and developed the instrument in the context of physical education (2010), and the context of badminton training (2012). The results of this study show a probability value of 0.240 for gender, 0.974 types of sports and 0.365 interactions, both greater than 0.05, then Ho is accepted. This means that there is no influence of gender, type of sport and their interaction on extrinsic motivation and intrinsic motivation of students in participating in sports UKM.